Enhanced Antibody Production in Clever-1/Stabilin-1–Deficient Mice - Dunkel, Johannes; Viitala, Miro; Karikoski, Marika; Rantakari, Pia; Virtakoivu, Reetta; Elima, Kati; Hollmén, Maija; Jalkanen, Sirpa; Salmi, Marko (Frontiers in Immunology, 2018)
Clever-1, encoded by the Stab1 gene, is a scavenger and leukocyte trafficking receptor expressed by subsets of vascular and lymphatic endothelial cells and immunosuppressive macrophages. Monocyte Clever-1 also modulates T cell activation. However, nothing is known about the possible links between B cell function and Clever-1. Here, we found that Stab1 knockout mice (Stab1−/−) lacking the Clever-1 protein from all cells present with abnormally high antibody levels under resting conditions and show enhanced humoral immune responses after immunization with protein and carbohydrate antigens. Removal of the spleen does not abolish the augmented basal and post-immunization levels in Clever-1–deficient mice. The increased IgG production is also present in mice in which Clever-1 is selectively ablated from macrophages. When compared to wildtype macrophages, Clever-1–deficient macrophages show increased TNF-α synthesis. In co-culture experiments, monocytes/macrophages deficient of Clever-1 support higher IgM production by B cells, which is blocked by TNF-α depletion. Collectively, our data show that the excessive inflammatory activity of monocytes/macrophages in the absence of Clever-1 results in augmented humoral immune responses in vivo.